PENGARUH MODEL PEMBELAJARAN EVERYDAY MATHEMATICS (EM) TERHADAP KEMAMPUAN BERFIKIR KRITIS DAN KREATIF SISWA SMP NEGERI 01 LEBONG - Dona Eka Safitriyanti; Hari Sumardi; Saleh Haji (LPPM Universitas Bina Bangsa, 2023)
This study aims to determine the effect of the Everyday Mathematics (EM) Learning Model on Students' Critical and Creative Thinking Ability. This type of research uses the Quasi Experiment method. Data collection is done through tests. Data analysis used the Ancova test. The sample of this research is students of SMPN 01 Lebong class VII.4 and VII.6. The results showed that: There is a linear influence of initial ability covariates on students' critical thinking skills with an effect of 62.6%. There is a linear influence of initial ability covariates on students' creative thinking abilities with an effect of 22.7%. There is an effect of applying the Everyday Mathematics learning model to students' critical thinking skills with an effect of 82.9%. There is an effect of applying the Everyday Mathematics learning model to students' creative thinking abilities with an effect of 6.5%. the achievement of critical thinking skills taught through learning using the Everyday Mathematics learning model is better than that taught through conventional learning. the achievement of creative thinking skills taught through learning using the Everyday Mathematics learning model is better than that taught through conventional learning